A numerical insight on machining burr formation: A comprehension to optimization approach. (2020) - Asad, Muhammad; Ijaz, Hassan; Khan, Muhammad Azhar Ali; Asghar yaseen, Asim; Waqar, Taha; Aziz Afzal, Abdul
Abstract: An insight into comprehension and optimization of exit burr formation in orthogonal machining case is presented in the work. Formation of exit burr has been simulated using a three dimensional FE based machining model. Variation of "pivot-point" (point of maximum bending stress, appearing at workpiece exit edge) location on workpiece end and its appearance with respect to tool position during cutting process has been correlated with burr formation process. To minimize the burr formation, machining process variables (including speed, feed and tool rake angle) optimization have been realized employing Abaqus®. Burr lengths at exit end along workpiece depth of cut (ap ) are quantified and optimum machining parameters generating less burrs for dry machining of AA2024 are identified. Simulated results pertaining to chip and cutting forces are fairly matched with related experimental results in the published literature.